2006
DOI: 10.1158/0008-5472.can-06-2379
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human CD8 on Antigen Recognition by T-Cell Receptor–Transduced Cells

Abstract: The CD8 coreceptor on T cells has two functions. Namely, CD8 acts to stabilize the binding of the T-cell receptor (TCR) to the peptide-MHC complex while localizing p56 lck (lck) to the TCR/CD3 complex to facilitate early signaling events. Although both functions may be critical for efficient activation of a CTL, little is known about how the structural versus signaling roles of CD8, together with the relative strength of the TCR, influences T-cell function. We have addressed these issues by introducing full-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 43 publications
(85 reference statements)
2
42
0
Order By: Relevance
“…In contrast, disruption of the synergistic extracellular binding effects and intracellular coreceptor functions of CD8 in the system of Holler and Kranz probably resulted in a higher stringency of coreceptor dependence. A recent study suggested that the signaling properties of CD8 act in synergy with the TCR/pMHCI stabilization effect and are likely to have a dominant effect in the overall enhancement of the antigen sensitivity phenomenon conferred by the coreceptor (49). The difference of coreceptor dependence affinity thresholds observed in our study and in that of Holler and Kranz fits well with this concept.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, disruption of the synergistic extracellular binding effects and intracellular coreceptor functions of CD8 in the system of Holler and Kranz probably resulted in a higher stringency of coreceptor dependence. A recent study suggested that the signaling properties of CD8 act in synergy with the TCR/pMHCI stabilization effect and are likely to have a dominant effect in the overall enhancement of the antigen sensitivity phenomenon conferred by the coreceptor (49). The difference of coreceptor dependence affinity thresholds observed in our study and in that of Holler and Kranz fits well with this concept.…”
Section: Discussionsupporting
confidence: 88%
“…Generation of CD8 + Jurkat cells has been described previously (19,47). Briefly, a modified SAMEN retroviral vector containing full-length human CD8 α and β, separated by an internal SRα promoter, and an internal ribosome entry site/neo r cassette was used to transduce cells.…”
Section: Discussionmentioning
confidence: 99%
“…Jurkat cells, CD8 + Jurkat cells, and anti-CD3-activated primary T cells were transduced to express HCV1406 TCR via spinoculation, as previously described (20,22,47,48). Briefly, 0.5 mL per well of 30 μg/mL retronectin was used to coat 24-well, flat-bottom, nontissue culture-treated plates overnight at 4°C.…”
Section: Discussionmentioning
confidence: 99%
“…phorbol myristate acetate, PMA), for maximal IL-2 production. Jurkat cells expressing tyrosinase-specific TCR and αβCD8, α′β′CD8 or no CD8 were prepared as described [16]. T2 cells are a Tap-1 −/− human B/T cell lymphoma.…”
Section: Methodsmentioning
confidence: 99%